2013
DOI: 10.3399/bjgp13x670660
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events recorded in English primary care: observational study using the General Practice Research Database

Abstract: BackgroundMore accurate and recent estimates of adverse events in primary care are necessary to assign resources for improvement of patient safety, while predictors must be identified to ameliorate patient risk. AimTo determine the incidence of recorded iatrogenic harm in general practice and identify risk factors for these adverse events. Design and settingCross-sectional sample of 74 763 patients at 457 English general practices between 1 January 1999 and 31 December 2008, obtained from the General Practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
2
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 43 publications
(50 reference statements)
4
33
2
4
Order By: Relevance
“…Medication‐related problems have been identified from various sources in the literature including incident reporting by healthcare professionals, medico‐legal and patient complaints and systematic identification of organisational structure (Department of Health ; Tsang, Bottle, Majeed, & Aylin, ; Wallace, Lowry, Smith, & Fahey, ).…”
Section: Introductionmentioning
confidence: 99%
“…Medication‐related problems have been identified from various sources in the literature including incident reporting by healthcare professionals, medico‐legal and patient complaints and systematic identification of organisational structure (Department of Health ; Tsang, Bottle, Majeed, & Aylin, ; Wallace, Lowry, Smith, & Fahey, ).…”
Section: Introductionmentioning
confidence: 99%
“…Certain age groups and clusters of diseases place patients at increased risk. Little is known of the effect of polypharmacy and patterns of prescribing on multimorbid patients [49]. Our initial analysis showed that almost 62% of patients in our sample were prescribed drugs for which some form of interaction is known; strongly interacting for nearly 40%.…”
Section: Discussionmentioning
confidence: 95%
“…In the Organisation for Economic Co-operation and Development’s member countries, 9% of hospitalized patients [1] suffer an adverse event, whereas studies in primary care centers have identified a rate of adverse events of less than 2% for all consultations [3,4]. At hospitals and primary care centers, 18% and 7% of patients, respectively, experienced more than 1 adverse event [4,5].…”
Section: Introductionmentioning
confidence: 99%